Предмет: Алгебра,
автор: SadChill
(c-2)^2(c+2)-(c+2)(c-2) упростить выражение
Ответы
Автор ответа:
0
(с-2)²(с+2)-(с+2)(с-2) = (с²-4с+4)(с+2)-(с²-4) = с³+2с²-4с²-8с+4с+8-с²+4 = с³-3с²-4с+12
matilda17562:
Проверьте, пожалуйста, ответ. -8с + 4с = -4с
Автор ответа:
1
Решение:
(c-2)²·(c+2) - (c+2)·(c-2) = (c-2)·(c+2)·(c-2-1) = (c² - 2²) ·(c-3) = (c² - 4)·(c-3) = c³ - 3c²- 4c + 12.
(c-2)²·(c+2) - (c+2)·(c-2) = (c-2)·(c+2)·(c-2-1) = (c² - 2²) ·(c-3) = (c² - 4)·(c-3) = c³ - 3c²- 4c + 12.
Похожие вопросы
Предмет: Математика,
автор: ajsarasubarova
Предмет: Математика,
автор: nstarovojtov2011
Предмет: Математика,
автор: angelina12053
Предмет: История,
автор: вера217
Предмет: Химия,
автор: Nastya0416